2021
DOI: 10.1101/2021.03.14.21253537
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Famotidine on Hospitalized Patients with COVID-19: a Systematic Review and Meta-analysis

Abstract: Introduction: Famotidine is a competitive histamine H2-receptor antagonist most commonly used for gastric acid suppression but thought to have potential efficacy in treating patients with COVID-19. The aims of this systematic review and meta-analysis are to summarize the current literature and report clinical outcomes on the use of famotidine for treatment of hospitalized patients with COVID-19. Methods: Five databases were searched through February 12, 2021 to identify observational studies that reported on a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Other purported extraintestinal benefits of H2RAs are far-reaching and include reduction of bladder pain from interstitial cystitis, improvement of cell-mediated immunity, and reduction of symptoms related to erythropoietic protoporphyria [42][43][44]. Furthermore, recent studies have demonstrated a potential role for H2RAs as an adjunctive treatment for COVID-19 [45,46]. To the best of our knowledge, this is the first large-scale study to assess the effect of H2RAs on mortality in the setting of sepsis.…”
Section: Discussionmentioning
confidence: 94%
“…Other purported extraintestinal benefits of H2RAs are far-reaching and include reduction of bladder pain from interstitial cystitis, improvement of cell-mediated immunity, and reduction of symptoms related to erythropoietic protoporphyria [42][43][44]. Furthermore, recent studies have demonstrated a potential role for H2RAs as an adjunctive treatment for COVID-19 [45,46]. To the best of our knowledge, this is the first large-scale study to assess the effect of H2RAs on mortality in the setting of sepsis.…”
Section: Discussionmentioning
confidence: 94%
“…However, in a meta-analysis of observational study famotidine has been shown is not associated with a reduced risk of mortality, intubation, and/or ICU admission in COVID-19 patients, but the heterogeneity of studies was high, and due to lack of power a possible protective effect has been proposed ( Chiu et al, 2021 ). On the other hand, in a randomized, double-blind, clinical trial famotidine has been shown that lead to earlier resolution of covid-19 symptoms and inflammation ( Brennan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%